2010
DOI: 10.1002/dc.21278
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the scope of conventional cervical cytology for detecting HPV infection

Abstract: Cervical neoplasia is attributed to a persistent Human Papilloma Virus infection. The Pap smear being the mainstay of cervical cancer screening in low-resource settings, we studied the nonclassical features which might indicate HPV infection. These included abortive koilocytes, mild dyskeratosis, parakeratosis, mild nuclear hyperchromasia, bi/multinucleation, measles cells, and keratohyaline-like granules. Two hundred and eight women with a satisfactory Pap smear and a Hybrid Capture II test were compared agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…Therefore, it is possible that cytotechnologists are intuitively considering not only the increase in chromatin but also nuclear contour thickening as a criterion for distinguishing atypical cells from NILM. [18][19][20][21] Furthermore, we found that the smaller the area ratio of the nuclear enlarged cells, the greater the nuclear contour thickening. Therefore, to infer infection with high-risk HPV from the morphology in Pap test samples, it may be necessary to focus not only on cells with enlarged nuclei but also on nuclear contour thickening.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Therefore, it is possible that cytotechnologists are intuitively considering not only the increase in chromatin but also nuclear contour thickening as a criterion for distinguishing atypical cells from NILM. [18][19][20][21] Furthermore, we found that the smaller the area ratio of the nuclear enlarged cells, the greater the nuclear contour thickening. Therefore, to infer infection with high-risk HPV from the morphology in Pap test samples, it may be necessary to focus not only on cells with enlarged nuclei but also on nuclear contour thickening.…”
Section: Discussionmentioning
confidence: 61%
“…Additionally, while we showed significant differences between squamous cells with enlarged nuclei in ASC‐US and NILM cases, the nuclear area ratio difference was only about 0.30. Therefore, it is possible that cytotechnologists are intuitively considering not only the increase in chromatin but also nuclear contour thickening as a criterion for distinguishing atypical cells from NILM . Furthermore, we found that the smaller the area ratio of the nuclear enlarged cells, the greater the nuclear contour thickening.…”
Section: Discussionmentioning
confidence: 70%
“…AKs were defined as superficial or intermediate cells that met only one or two of these conditions, showing some perinuclear cytoplasmic clearing, but lacking the large, sharply demarcated pNcH surrounded by a condensed cytoplasmic rim and nuclear atypia 12,13. The degree of AKs was coded according to the total number of AKs in the specific selected lesion as follows: 0, no AKs; 1, AK is ≄1 but <10; 2, AK is ≄10 but <20; 3, AK ≄20.…”
Section: Methodsmentioning
confidence: 99%
“…As already described in the literature, the correlation between both cytopathologists was poor as well as the sensitivity if compared with the PCR results. Authors focusing on the detection of HPV by cytomorphology alone reported better results; however, many cytomorphological features were applied in these studies …”
Section: Discussionmentioning
confidence: 99%